Peptide nucleic acid (PNA) binding-mediated induction of human gamma-globin gene expression. - Wang, G (1999)
Peptide nucleic acids (PNAs) can bind to homopurine/homopyrimidine sequences of double-stranded DNA targets in a sequence-specific manner and form [PNA]2/DNA triplexes with single-stranded DNA D-loop structures at the PNA binding sites. These D-loop structures have been found to have a capacity to initiate transcription in vitro. If this strategy can be used to induce transcription of endogenous genes, it may provide a novel approach for gene therapy of many human diseases. Human [beta] globin disorders such as sickle cell anemia and beta-thalassemia are very common genetic diseases that are caused by mutations in the beta-globin gene. When gamma-globin genes are highly expressed in sickle cell patients, the presence of high levels of fetal hemoglobin (HbF, alpha2gamma2) can compensate for the defective beta-globin gene product and such patients have much improved symptoms or are free of disease. However, the gamma-globin genes are developmentally regulated and normally expressed at very low levels (>1%) in adult blood cells. We have investigated the possibility of inducing gamma-globin gene expression with PNAs. Using PNAs designed to bind to the 5' flanking region of the gamma-globin gene, induction of expression of a reporter gene construct was demonstrated both in vitro and in vivo. More importantly, PNA-mediated induction of endogenous gamma-globin gene expression was also demonstrated in K562 human erythroleukemia cells. This result suggests that induction of gamma-globin gene expression with PNAs might provide a new approach for the treatment of sickle cell disease. PNA-induced gene expression strategy also may have implications in gene therapy of other diseases such as genetic diseases, cancer and infectious diseases.